Two cases of rheumatoid meningitis. Issue 1 (8th September 2015) - Magaki, Shino; Chang, Edward; Hammond, Robert R.; Yang, Isaac; Mackenzie, Ian R. A.; Chou, Benedict T.; Choi, Soo I.; Jen, Joanna C.; Pope, Whitney B.; Bell, David A.; Vinters, Harry V.
Abstract : Central nervous system (CNS) involvement by rheumatoid arthritis (RA) in the form of rheumatoid meningitis (RM) is rare and most commonly occurs in the setting of longstanding severe RA. Due to a wide range of clinical presentations and nonspecific laboratory findings, it presents a diagnostic challenge often requiring brain biopsy. Only a few histopathologically confirmed cases have been described in the literature. Our aim is to describe two cases of RM and review the literature. The first case is of a previously healthy 37‐year‐old man who presented with severe headaches and focal neurologic deficits. Magnetic resonance imaging demonstrated abnormal leptomeningeal enhancement in the left frontal and parietal sulci. The second case is of a 62‐year‐old woman with a history of mild chronic joint pain who presented with confusion, personality changes and seizures. Both patients ultimately underwent brain biopsy which demonstrated RM on pathologic examination. Administration of corticosteroids resulted in significant clinical improvement in both cases. To our knowledge, our unusual case of RM in the young man is the fifth reported case of rheumatoid meningitis in a patient with no prior history of RA. Such an atypical presentation makes diagnosis even more difficult and highlights the need for awareness of this entity in the diagnostic consideration of a patient presenting with unexplained neurologic symptoms. Our literature review underscores the clinical and pathologic heterogeneity of CNS involvement in RA.